2007
DOI: 10.1530/rep-07-0161
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell factor affects fate determination of human gonocytes in vitro

Abstract: The stem cell factor (SCF), binding its tyrosine kinase receptor c-Kit, has been shown to play essential roles in the proliferation, differentiation, and survival of germline cells. However, few reports are available about the effect of SCF on the development of human gonocytes within the fetal testis. The objective of this study was to investigate whether SCF affects the biological behaviors of human gonocytes before or after they enter the mitotic arrest stage. Employing an organ culture system, we observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…PGCs are positive for the receptor, and the SCF will function as a chemo-attractant, leading the cells to the genital ridge, their final destination. This signalling pathway has various functions, including survival by preventing induction of apoptosis (Tu et al, 2007). Interestingly, disturbances in this signalling pathway result in various anomalies, including abnormal migration of PGCs, possibly leading to infertility.…”
Section: Normal Germ Cell Development Before Entrance Into the Gonadmentioning
confidence: 99%
“…PGCs are positive for the receptor, and the SCF will function as a chemo-attractant, leading the cells to the genital ridge, their final destination. This signalling pathway has various functions, including survival by preventing induction of apoptosis (Tu et al, 2007). Interestingly, disturbances in this signalling pathway result in various anomalies, including abnormal migration of PGCs, possibly leading to infertility.…”
Section: Normal Germ Cell Development Before Entrance Into the Gonadmentioning
confidence: 99%
“…The ligand for c-KIT is the stem cell factor (SCF, KITLG) and the SCF-KIT pathway regulates the differentiation of melanocytes, red blood cells, mast cells, interstitial cells of Cajal, and germ cells [1], [2], [3]. Moreover, this pathway is important in the survival of primordial germ cells (PGCs) [4], [5]. Expression of c-KIT and gain-of-function mutations in c-KIT has been found in mastocytosis, leukemia and gastro-intestinal stromal tumors (GIST) [6], [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…For example, adding LIF enhanced PGC survival, but the observations with the use of other factors is not as clear. [258][259][260] Currently, it is not at all clear that these cells resemble their germ cell counterparts in vivo, but improvements in culture conditions and the cellular microenvironment will certainly help in this regard. 256 However, a landmark study has recently shown that supplementation of LIF in a "2i" cocktail for mESC growth can induce an epiblast-like cell stage of mESCs and set the stage for PGC development.…”
Section: Pgc Specificationmentioning
confidence: 99%